Chapter 27 Samhandling, Preparedness and Supply Chains - Listou, Tore (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"Supply-chain preparedness means to design inter-organisational structures, to organise supply-chain resources, and to plan and train to ensure efficient response if this is called for. Acknowledging that supply chains are made up of two or more organisations, and that interaction describes relations between two or more actors, the purpose of this research is to explore whether the introduction of the concept of interaction (samhandling) to supply-chain thinking adds to our understanding of efficiency and the effectiveness of logistics preparedness. We position our work along three dimensions: a profit - non-profit classification, a descriptive - normative dichotomy, and a micro - macro continuum. Information was retrieved both through semi-structured interviews and by studying secondary sources. Interaction and preparedness is assessed through an empirical case: the operation Atalanta. By applying interactional indicators, enablers and barriers to relationship success can be studied at both micro, meso, and macro levels. Without understanding the mechanisms leading to interactional competence, success (or the lack thereof) in supply-chain preparedness is difficult to address properly. Thus, managers need to assess the interactional constructs at all levels when planning and training for preparedness."